Antigenic evolution of dengue virus in Malaysia / Mohammed Bashar Danlami - Danlami, Mohammed Bashar (2014)
Neutralization escape mutant has played an important role in antigenic evolution of various virus-causing diseases. DENV, the causative agent of dengue has been shown to escape antibody neutralization, thereby causing an epidemic outbreak. The pattern through which DENV escape neutralization that leads to antigenic evolution, however, has not been thoroughly investigated in hyper endemic countries. It is hypothesized that, the highly susceptible DENV demonstrates a clear pattern of antigenic evolution from being minor strains (less frequent during an outbreak) to dominant strains (very frequent during an outbreak). This suggests that the minor strains may act as a springboard for the emergence of more virulent dominant strains by acquiring some characteristics of the minor strains. Hence, the overall objective of the present study is to provide an insight into the antigenic evolution of DENV-1 and DENV-2 in Malaysia. To investigate this possibility, the present study used truncated DENV-1 and DENV-2 recombinant E, cloned and expressed on phage M13 g3p attachment protein. Using site-directed mutagenesis, six single mutations were engineered separately onto the respective recombinant E gene. Effects of these mutations on binding to insects and mammalian cells were determined in vitro. The polyclonal antibodies generated against these recombinant proteins in BALB/c mice were used in microneutralization and Foci Reduction Neutralization Test to evaluate neutralizing antibody determinant associated with antigenic evolution. Serial propagation in vitro was adopted to handpick the neutralization escape mutant in the sub-neutralizing antibody concentration. To evaluate potential host where the selection occurs, the escape mutant were adapted to mimic mosquito and human cycle in vitro. Finding from the present study shows that two mutations (E272 and E390) on DENV-1 E were demonstrated to affect binding of the recombinant proteins to C6/36 mosquito and Vero cells. Polyclonal antibodies generated against recombinant E272 and E390 proteins exhibited decreased binding to DENV-1 virion. The polyclonal antibodies reduced the number of DENV-1 foci formed up to four-folds for the five endemic DENV-1 strains (GIa, GIb, GIc, GII and GIII) tested. Two DENV-1 isolates likely to escape neutralization were identified; D1.10245 (GII) and D1.11177 (GIb). In DENV-2, mutations on E52, E164 and E393 were demonstrated to affect binding of the recombinant proteins to C6/36 mosquito and Vero cells. Polyclonal antibodies generated in mice against recombinant E52, E164 and E176 exhibited decreased binding to DENV-2 (Asian 1 strain) and E164 and E335 on one of the Cosmopolitan strain. The polyclonal antibodies against E52, E71, E335 and E393 reduced the number of foci formed up to four-folds for Cosmopolitan DENV-2 strains tested. The E52 and E71 substitutions select isolates likely to escape neutralization in both Cosmopolitan strain (D2.14245 and D2.1877347) and Asian 1 strain (D2.16041). Evidence from the present study show that the neutralization escape strains from DENV-1 and DENV-2 alternating between two different hosts adapts differently. The observed difference in DENV-1 and DENV-2 on C6/36 and Vero cells was evident in the variation in amino acid residues on E. Of these 6 mutations engineered on DENV-1 and DENV-2 recombinant E, substitution on EDI/EDII junction are likely to facilitates antigenic evolution of DENV-1 (E272) and DENV-2 (E52 and E71) in Malaysia. Overall, the study identified dominant DENV-1 and DENV-2 strains expected to evolve in Malaysian natural population in the future. The antigenic determinants involved were identified. The result of the study directly underlines the effects of these mutations on naturally emerging DENV-1 and DENV-2 in Malaysian population and its implications on dengue affliction and vaccines design.